The Spirit and Its Thinking. On the Recepcion of Plato’s megista gēnē Doctrine in Plotinus and Proclus - Gögelein, Simon (Peitho. Examina Antiqua, 2014)
This article is primarily concerned with Platoʼs later dialogue, the Sophist, and the reception of the megista-gēnē-dialectic in Neoplatonism (especially Plotinus and Proclus). The present paper offers a historical comparative study that consists of three parts. The first one gives a short summary concerning Platoʼs request regarding the concept of inverse and complex Ideas. The second one examines Plotinus’ conception of the νοῦς (Enn. VI 2, 7–8), in which the megista gēnē στάσις, κίνησις, ὄν, ταὐτόν and ἕτερον constitute the realm of the intellect. While the third and final part of the article investigates Proclusʼ extrapolation of the Platonic dialectic, it focuses on selected passages from the Commentary on the Parmenides. The paper concludes with a summary of the results.